Survey on evacuation planning and preparation in psychiatric hospitals in Kagoshima Prefecture, Japan - Yanagida, Nobuhiko; Matsuda, Fumiyo; Inoue, Kazuhiro; Matsunari, Yuko (Japanese Journal of Disaster Medicine, 2024)
【Objective】 The purpose of this study was to identify evacuation issues faced by psychiatric hospitals in Kagoshima Prefecture in the event of a disaster, to ensure patient safety, and to strengthen post-disaster response. 【Methods】 In cooperation with the Kagoshima Prefecture Psychiatric Hospital Association, an online survey was conducted to investigate the preparedness for and challenges of evacuation actions in hospitals. In addition, the location of hospitals was compared with hazard maps and nuclear disaster warning zones. 【Results】 A wide variation was found in the development and implementation of evacuation action plans. Notably, many hospitals were still considering or had not conducted evacuation drills. This finding highlights the lack of consistent planning and practices for ensuring safety and providing evacuation support during disasters. Furthermore, the need for expert support and cooperation was identified as a common need along with inherent challenges. 【Conclusion】 For psychiatric hospitals to improve their disaster response measures, they should support development of evacuation action plans, conduct evacuation drills, improve the specificity and consistency of evacuation support, and strengthen cooperation with specialists.